Comparisons of Metastatic Patterns, Survival Outcomes and Tumor Immune Microenvironment Between Young and Non-Young Breast Cancer Patients - Sun, Hengwen; Huang, Wei; Ji, Fei; Pan, Yi; Yang, Lu (Frontiers in Cell and Developmental Biology, 2022)
Background: Metastases are the main cause of breast cancer-related deaths. Breast cancer has a more aggressive phenotype and less favorable prognosis in young females than in older females. In this study, we aimed to compare the metastatic patterns, survival outcomes and tumor immune microenvironment of young and non-young breast cancer patients. Methods: Patients with a diagnosis of breast cancer were identified from the Surveillance, Epidemiology, and End Results (SEER) database between 2010 and 2015. The significance of young age (≤40 years) in the metastatic profile and prognosis of breast cancer was investigated. The transciptome expression data were acquired from The Cancer Genome Atlas (TCGA) database. And the differentially expressed genes (DEGs) and primarily enriched function pathways were identified by comparing between young and non-young breast cancer samples, and tumor immune infiltrating cell types in the tumor microenvironment were compared. Results: A total of 281,829 female breast cancer patients were included in SEER: 18,331 young (6.5%) and 263,498 non-young (93.5%) women. The metastatic rates of bone, liver and distant lymph nodes (DLNs) in the young cohort were significantly higher than those in the non-young cohort. The most frequent two-site metastatic combination was bone and liver (0.61%) in the young cohort, whereas it was bone and lung (0.32%) in the non-young cohort. Breast cancer-specific survival (BCSS) was significantly shortened among those in the young cohort compared with those in the non-young cohort (P<0.001). Young age was associated with significantly shorter BCSS only among patients with HR+/HER2- tumors (P<0.001). The enriched biological pathways based on DEGs between two cohorts were related to the regulation of immune response and several metabolic processes. M2 macrophages were significantly abundant in non-young breast cancer than young breast cancer. Conclusions: Young and non-young breast cancer patients present with different metastatic patterns. Young age is a negative prognostic factor, particularly for HR+/HER2- breast cancer. The differences in metastatic patterns between young and non-young cohorts should be taken into account in the clinical management of metastatic breast cancer. The young breast cancer patients may gain better response to immunotherapy due to immune activated TME than non-young breast cancer.